Synergistic increase in coproporphyrin III biosynthesis by mitochondrial compartmentalization in engineered Saccharomyces cerevisiae - Qidi Guo; Jiaqi Xu; Jiacun Li; Shuyan Tang; Yuhui Cheng; Bei Gao; Liang-Bin Xiong; Jie Xiong; Feng-Qing Wang; Dong-Zhi Wei (Synthetic and Systems Biotechnology)
Coproporphyrin III (CP III), a natural porphyrin derivative, has extensive applications in the biomedical and material industries. S. cerevisiae has previously been engineered to highly accumulate the CP III precursor 5-aminolevulinic acid (ALA) through the C4 pathway. In this study, a combination of cytoplasmic metabolic engineering and mitochondrial compartmentalization was used to enhance CP III production in S. cerevisiae. By integrating pathway genes into the chromosome, the CP III titer gradually increased to 32.5 ± 0.5 mg/L in shake flask cultivation. Nevertheless, increasing the copy number of pathway genes did not consistently enhance CP III synthesis. Hence, the partial synthesis pathway was compartmentalized in mitochondria to evaluate its effectiveness in increasing CP III production. Subsequently, by superimposing the mitochondrial compartmentalization strategy on cytoplasmic metabolic engineered strains, the CP III titer was increased to 64.3 ± 1.9 mg/L. Furthermore, augmenting antioxidant pathway genes to reduce reactive oxygen species (ROS) levels effectively improved the growth of engineered strains, resulting in a further increase in the CP III titer to 82.9 ± 1.4 mg/L. Fed-batch fermentations in a 5 L bioreactor achieved a titer of 402.8 ± 9.3 mg/L for CP III. This study provides a new perspective on engineered yeast for the microbial production of porphyrins.